2019
DOI: 10.1590/2317-1545v41n1191945
|View full text |Cite
|
Sign up to set email alerts
|

Environmental stress, future climate, and germination of Myracrodruon urundeuva seeds 1

Abstract: Myracrodruon urundeuva, a native species from the Brazilian Caatinga, is widely distributed across its endemic region, where it also plays an essential socioeconomic role. The objective of this study was to evaluate the influence of environmental stress on the germination of M. urundeuva seeds harvested in different years (2010 to 2013). Seeds were germinated at constant temperatures between 10 to 40 °C, osmotic potentials from 0 to -0.8 MPa (in polyethylene glycol 6000 solutions), and from 0 to -0.5 MPa (in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 32 publications
3
23
0
1
Order By: Relevance
“…In this study, the temperature thresholds, as well as the sub and supra-optimum thermal times of the species, showed that they can germinate in a wider temperature range after ondergoing HD cycles, obtaining with T b below 10 °C and T c above 40 °C. Agreeing to our results, studies on seeds native to the Caatinga reported that different species and all seed lots (from different harvests and provenances) germinated in a wide thermal range, with T b below 10 °C and/or T c above 40 °C (Gomes et al, 2019;Oliveira et al, 2019;Dantas et al, 2020).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…In this study, the temperature thresholds, as well as the sub and supra-optimum thermal times of the species, showed that they can germinate in a wider temperature range after ondergoing HD cycles, obtaining with T b below 10 °C and T c above 40 °C. Agreeing to our results, studies on seeds native to the Caatinga reported that different species and all seed lots (from different harvests and provenances) germinated in a wide thermal range, with T b below 10 °C and/or T c above 40 °C (Gomes et al, 2019;Oliveira et al, 2019;Dantas et al, 2020).…”
Section: Resultssupporting
confidence: 84%
“…Seeds GR has been studied on different species subjected to several factors, such as storage time, water deficit and different temperatures, in order to obtain the germination thresholds (Oliveira et al, 2019;Gomes et al, 2019;Daibes and Cardoso, 2020). In this study, the temperature thresholds, as well as the sub and supra-optimum thermal times of the species, showed that they can germinate in a wider temperature range after ondergoing HD cycles, obtaining with T b below 10 °C and T c above 40 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature and water potential show important interactions to describe germination parameters under laboratory conditions (Alvarado and Bradford, 2002). However, few studies were accounted for such interactions (hydrothermal time) in Brazilian species (Simão et al, 2010;Oliveira et al, 2019). Seedling emergence from soil seedbanks should also be examined, in order to validate such models under field conditions (Forcella et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Concerning native species, few studies in current literature investigated such threshold models regarding water relations and seed germination of tropical trees (Daws et al, 2008). Some studies evaluated the role of Ψ on seed germination of Brazilian species (Botelho and Perez, 2001;Fonseca and Perez, 2003;Rego et al, 2007), but rarely explaining whether germination would fit the presupposes of hydrotime models (Cardoso and Pereira, 2008;Oliveira et al, 2019). Most attention regards to the role of temperature, rather than water potential, as described by thermal time models in neotropical species (Cardoso and Pereira, 2009;Pires et al, 2009;Daibes and Cardoso, 2018;Duarte et al, 2018).…”
Section: Introductionmentioning
confidence: 99%